Role of Phoenix dactylifera (Ajwa) on lipid profile; a randomized controlled trial - Naseer Ahmed; Javeria Farooq; Sultan Ayoub Meo; Farooq Pasha (Journal of King Saud University: Science, 2022)
Objective: Date palm is a significant crop mainly of hot regions and used as a traditional remedy for various ailments. Ajwa is a well-known functional food with an abundance of phytochemicals that possess different beneficial and medicinal properties. The study's objective was to calculate the impact of Ajwa consumption in a daily routine on lipid profile and HDL in the general population. Methods: Randomized clinical trial was conducted for six weeks on participants, including both genders, with HDL levels below 40 mg/dl. The intervention group was advised to take Ajwa (70 gm) on an empty stomach in the morning for five days a week for six consecutive weeks with their routine diet and physical activity. The control group was advised not to make any changes in their diet and everyday life. Body weight, BMI, blood glucose, and lipid levels were recorded before and after the trial to evaluate the effect of Ajwa on these markers. Result: The Ajwa intervention group showed a significant effect for total cholesterol, triglycerides, LDL, and HDL (p = 0.001), representing that the Ajwa group showed more alterations than the control group. However, no significant interaction effect was identified for body weight, BMI, and blood glucose level for both Ajwa and the control group. Conclusion: The study findings recommend that intake of Ajwa is well tolerated, and its inclusion in diet and routine life provides cardioprotection by improving the lipid profile and raising the sub-optimal HDL levels.